Optimal Use of the Forum to Develop Problem-Based Learning: Effective Use of Cyber space in a Holistic Process (Bangladesh Journal of Medical Science, 2017)
Introduction: Many medical schools have introduced PBL into their curricula because of the potential advantages for students learning over traditional lecture based curricula. Integration of online discussion forums could help students, PBL and the curriculum. The aim of this article is the use of the Forum to Develop Problem-Based Learning as a Cyberspace in a Holistic Process and the investigating the effect of this program on students satisfaction and students cognitive competence.Methodology: For each curriculum used a discussion forum (DF) was created with 90 student and 8 tutors. Using forum for problem based learning- virtual quiz and virtual round develop and design to develop problem based learning and the best use of virtual space to promote teaching and learning also best use of technology in teaching as a new method.Results: Included: reforming and finalizing learning objectives, posting the concept map constructed in the face-to-face session and questioning, encouraging and motivating each other. In addition, posts included tutors feedback and redirection.Conclusions: Blending e-learning with conventional PBL may help overcome student-perceived shortcomings of conventional PBL and improve the learning experience, making learning more interactive and interesting.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.564-571